miR-152 as a tumor suppressor microRNA: Target recognition and regulation in cancer - LIU, XUEXIANG (Oncol Lett, 2016)
MicroRNAs (miRNAs or miRs) are endogenous translation repressors of protein-coding genes that act by binding to the 3′-untranslated region of their target genes, and may contribute to tumorigenesis by functioning as oncogenes or tumor suppressor genes. miR-152, a member of the miR-148/152 family, is aberrantly expressed in various diseases, including various types of cancer. A growing body of evidence has demonstrated that miR-152 may act as a tumor suppressor gene by regulating its target genes, which are associated with cell proliferation, migration and invasion in human cancer. In the present review, the gene structure and functions of miR-152 are discussed, and in particular, its regulatory mechanism, experimentally validated targets and tumor suppressor role in cancer, are highlighted.